Perubahan Struktur Sosial & Problem Sosial Dari Teknologi Informasi Dan Komunikasi (TIK) Di Indonesia - Heidy Arviani (Jurnal Ilmu Komunikasi, 2019)
Information and communication technology (ICT) develops very rapidly and gives color to the dynamics of social structures. The presence of a new communication technology always has an impact and stimulates change. The consequences of both desirable impacts and undesirable impacts must be ready for us to face. The technological relations of the First World and Third World countries are quite problematic because of the gaps and the accompanying political economy environment. The Indonesian context with its unique combination of society (agrarian, industrial & information) is increasingly fragmented with the development of this ICT. Indonesia must immediately adapt and solve all challenges both culturally, economically and politically. Technology always brings change, is not neutral and cannot be universal.